Propuesta en el bloque curricular en área de la Educación Física en Bachillerato General Unificado - Arias Escudero, Álvaro Javier (2023)
The proposal to the curricular block in the baccalaureate is observed through the performance that the student has in his physical abilities, with the objective of analyzing the situation and giving the student the perspective and the tool to have an active life, complying with the profile that comes out of the Ecuadorian bachelor. The investigation was carried out from a starting point, with the analysis of the data obtained through the physical tests of: speed, strength, heart rate, flexibility and motor coordination. The research sample consisted of third-year high school students from fiscal and fiscal institutions, as well as first-semester students at the Universidad Nacional de Chimborazo (UNACH). It was evaluated through the tests of; speed 5 x 10 meters, Ruffier Dickson test, medicine ball throw, sit-ups for 30 seconds, horizontal jump, sit and reach test and motor coordination test. The results were recorded by noting on a data record sheet, based on a table of scales for young people from 16 to 18 years of the different physical tests, comparing them and placing them by levels from 1 to 10, where 1 indicates low performance and 10 the highest performance, it is necessary to find an average level located at level 5 and 6 of the scale table for each student. The results were not very favorable in carrying out the test, in the execution of each physical capacity, therefore, there is no optimal level in its development. With the proposed proposal, we want the bachelor to incorporate the learning of the indicated body movements based on physical exercise, so that he becomes an active entity inside and outside his student life, through this it would reinforce the exit profile of the same, reaching an empirical learning about physical activity.